Principal’s Strategy in Implementing Organizational Communication at Madrasah Ibtidaiyah - Retno Pringadi; Mesiono Mesiono; Sri Rezeqi Rafiqah; Wardah Manurung; Azmar Azmar; Hendriyal Hendriyal (Universitas Pahlawan Tuanku Tambusai, 2023)
The communication strategy is the main capital for the head of the madrasa in forming a conducive learning climate in the madrasa. This study aims to analyze the principal's strategy in implementing organizational communication at Madrasah Ibtidaiyah (MI) Kesuma LKMD, Namorambe District. This study used a qualitative approach with an analytical descriptive method. Collecting data using the method of observation, interviews and document study. The results of this study conclude that the implementation of organizational communication strategies (vertical, horizontal, diagonal) in MI Kesuma LKMD Jatikesuma is in a good category, as seen in the following conditions: (1) Vertical communication in madrasas is not good enough, due to the lack of presence of the head schools in the process of teaching and learning activities; (2) Horizontal communication in the Jatikesuma madrasah is quite good. The high level of interaction among members of the same level and the still weak organizational cooperation indicates that the interaction is carried out more on non-formal communication. (3) Diagonal communication in madrasas is carried out well, because all members of the organization at different levels of position are given the freedom to communicate, both formal and non-formal.